Conceptual Design of Business Model Canvas Mobile Battery Swap Charging Station - Renny Rochani; Wahyudi Sutopo; Roni Zakaria; Fakhrina Fahma (Jurnal Ilmiah Teknik Industri, 2023)
The users of electric motorcycle in Indonesia are currently still limited. This is due to three main things, namely the limited amount of energy charging infrastructure, the lack of socialization regarding the knowledge of technical aspects of electric motorcycle and the financing aspects of electric motorcycle ownership. This research develops a conceptual design business model canvas of Mobile Battery Swap Charging Stations (MBSCS) for electric motorcycles which aim to find solutions to the three problems above. The development of the MBSCS model is an alternative to increase the number of electric charging infrastructure quickly, because the advantages of MBSCS include having a higher level of flexibility and simpler installation than Fixed Charging Stations. This research combines the need of increasing infrastructure and improving socialization to the community regarding the advantages of using electric motorcycle through marketing communication media. Increasing the understanding of technical aspects of electric motorcycle is expected to increase people's motivation to adopt electric motorcycle. This research uses secondary data to explore MBSCS business canvas model (BMC), MBSCS ecosystem, and MBSCS prototype design. The analysis illustrates the MBSCS ecosystem that align with the motorcycle users in Indonesia.  The existence of MBSCS is expected to significantly increase the buying interest, adoption, and diffusion of electric motors more broadly.